CAHPS and Comments: How Closed-Ended Survey Questions and Narrative Accounts Interact in the Assessment of Patient Experience. (March 2017) - Martino, Steven C; Shaller, Dale; Schlesinger, Mark; Parker, Andrew M; Rybowski, Lise; Grob, Rachel; Cerully, Jennifer L; Finucane, Melissa L
Objectives: To investigate whether content from patient narratives explains variation in patients' primary care provider (PCP) ratings beyond information from the closed-ended questions of the Consumer Assessment of Healthcare Providers and Systems (CAHPS) Clinician and Group Survey and whether the relative placement of closed- and open-ended survey questions affects either the content of narratives or the CAHPS composite scores. Methods: Members of a standing Internet panel (N = 332) were randomly assigned to complete a CAHPS survey that was either preceded or followed by a set of open-ended questions about how well their PCP meets their expectations and how they relate to their PCP. Results: Narrative content from healthier patients explained only an additional 2% beyond the variation in provider ratings explained by CAHPS composite measures. Among sicker patients, narrative content explained an additional 10% of the variation. The relative placement of closed- and open-ended questions had little impact on narratives or CAHPS scores. Conclusion: Incorporating a protocol for eliciting narratives into a patient experience survey results in minimal distortion of patient feedback. Narratives from sicker patients help explain variation in provider ratings.